2017
DOI: 10.1080/10962247.2017.1329172
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal and seasonal variations of odor and gas emissions from a naturally ventilated free-stall dairy barn on the Canadian prairies

Abstract: Diurnal and seasonal variations of odor, NH, and HS concentrations and emissions were monitored for a naturally ventilated dairy barn in a cold region. The emission factors were calculated and indoor air quality was evaluated. The overall odor and NH concentrations were higher in winter, whereas emissions were higher in the mild and warm seasons. Diurnal variation was most significant for odor emission in the mild season, when the ratio of maximum to minimum value was up to 4.6. The results can be used to esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 35 publications
(56 reference statements)
0
4
0
Order By: Relevance
“…In the current study, a positive monocausal correlation trend was found between NH 3 emission factors and both the ambient air temperature at the height of 1.5 m and the air temperature inside the flux chamber (r = 0.59 and 0.60, respectively, p < 0.001, n = 35). Based on continuous measurements of ammonia, it has been shown that indoor temperature, air velocity, and animal activity are the most relevant influencing factors that affect ammonia emission (Arogo et al 2003;Blanes-Vidal et al 2008;Flesch et al 2009;Hayes et al 2006;Huang and Guo 2017;Schauberger et al 2013;Ye et al 2011). Saha et al (2014) addressed the significant effect of relative humidity on the NH 3 emissions from a naturally ventilated dairy barn.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, a positive monocausal correlation trend was found between NH 3 emission factors and both the ambient air temperature at the height of 1.5 m and the air temperature inside the flux chamber (r = 0.59 and 0.60, respectively, p < 0.001, n = 35). Based on continuous measurements of ammonia, it has been shown that indoor temperature, air velocity, and animal activity are the most relevant influencing factors that affect ammonia emission (Arogo et al 2003;Blanes-Vidal et al 2008;Flesch et al 2009;Hayes et al 2006;Huang and Guo 2017;Schauberger et al 2013;Ye et al 2011). Saha et al (2014) addressed the significant effect of relative humidity on the NH 3 emissions from a naturally ventilated dairy barn.…”
Section: Discussionmentioning
confidence: 99%
“…Many gas and odor studies relating source emissions and/or concentration and downwind concentrations relied on periodic daytime measurements [22,[38][39][40]. Based on the dairy and swine case studies, periodic daytime sampling is more likely to capture maximum gas and odor emission rates but does not capture the peak downwind concentrations-more likely to cause annoyance.…”
Section: Discussionmentioning
confidence: 99%
“…The relative humidity of the air is high at different times of the year. Cowshed air quality is worse during the cold season [16][17][18][19]. This is due to the reduced ventilation intensity being too low to avoid low temperatures.…”
Section: Introductionmentioning
confidence: 99%